Profit Redistribution in Family-controlled, Group-affiliated Publicly-listed Corporations in Malaysia - Ng, Sin Huei; Shrives, Philip; Yeoh, Ken Kyid (Virtus interpress, 2013)
This paper attempts to examine the potential occurrence of profit redistribution in family-controlled business groups in Malaysia. It is argued that there exists a tendency for business groups with extensive family ownership and control to redistribute resources from group affiliates that outperformed to affiliates that underperformed. This phenomenon is prevalent particularly in large business groups where the link between business groups and politics is most clearly displayed. Such ‘propping up’ activities are believed to adversely affect the shareholders of the outperforming affiliates as the performance of these affiliates diminishes due to the profit redistribution. They also result in inefficient allocation of resources within the business group, though it is found that higher board independence may reduce such inefficiency.